India’s pearl millet seed industry: Prospects for high-iron hybrids - Karandikar, Bhushana; Smale, Melinda; Birol, Ekin; Tadla-Diressie, Michael (International Food Policy Research Institute, 2018)
In this paper, we seek to understand the current structure of the pearl millet seed sector in order to formulate recommendations about how best to position the marketing strategy for soon-to-be-released, high-iron hybrids. We conduct a thorough review of the literature, with reference to both qualitative and quantitative information. We focus on the evolution of the industry structure for pearl millet seed, documenting changes that have occurred in procedures for variety release and registration over time. We shed light on issues such as why some varieties are more popular than others; the role of companies in promoting varieties; and whether the rights of a high-iron hybrid should be exclusive to one company. We also explore the implications of the fact that neither farmers nor consumers can observe the high-iron trait for marketing and promoting new varieties. Our review leads us to recommend the development of a range of high-iron hybrids with varying genetic base and adaptation, as well as food and fodder traits. Demand-pull mechanisms should be integrated into the current public distribution system, and private seed companies incentivized through various means. The role of pearl millet in the livestock feed industry is worth of policy attention by HarvestPlus and partners.